Porang's Marketing Margin in the Agroforestry Program in Ngawi District, East Java - Anang Susanto; Indah Rekyani Puspitawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Porang is a plant widely developed under forest stands and on community land with an agroforestry pattern that lives around the forest. However, the community has yet to exploit porang as a business unit to meet food needs but only used it to fulfill daily needs. The research aims to analyze marketing margins and people's profit margins. Data was collected through field observations and interviews with 100 respondents, who were determined by purposive sampling. First, a descriptive analysis was carried out to describe the marketing channel of Porang, and then a study of marketing margins and profit margins was carried out. Based on data analysis, there are two marketing channels for porang: channel one, where farmers sell porang directly to consumers, and channel 2, where the marketing of porang is through intermediary traders. The first channel has no marketing margin and profit margin value minimum of IDR 1,200 and maksimum IDR OF 1,800, while in channel 2, porang marketing has a marketing margin maksimum value of IDR 6,500 and a profit margin minimum of IDR 4,500